A rapid cleaning method for diatoms. Issue 2 (3rd April 2019) - Trobajo, Rosa; Mann, David G.
Abstract : We describe here a protocol for cleaning diatoms when time is short and the amount of sample is very limited. Essentially, the method consists of drying material onto coverslips and cleaning it directly in situ using nitric acid (or hydrogen peroxide), which is evaporated to dryness. After washing twice or a few times with deionized water, the coverslips are ready for mounting in resin for light microscopy as usual, or attachment to stubs for scanning electron microscopy. Besides speed, the method has the advantage that it often preserves some frustules intact or leaves their different elements (and stages of valve formation) closely associated with each other. Examples where the method is especially advantageous are to clean small aliquots of cultures for identification or to act as vouchers, or to explore diversity of the most abundant species in natural material (e.g., periphyton). It is less suitable for counts in ecological or palaeoecological studies. We tabulate the many other cleaning methods to provide context for the new method described here.